Cover Image, Volume 113, Number 12, December 2016. Issue 12 (December 2016) - Khabou, Hanen; Desrosiers, Mélissa; Winckler, Céline; Fouquet, Stéphane; Auregan, Gwenaëlle; Bemelmans, Alexis‐Pierre; Sahel, José‐Alain; Dalkara, Deniz
Abstract : Cover Legend A schematic representation of cell transduction with AAV particles. The cover image, by Deniz Dalkara et al., is based on the Article Insight into the mechanisms of enhanced retinal transduction by the engineered AAV2 capsid variant ‐7m8, DOI:10.1002/bit.26031 .